THE DIGITAL ERA OF MARKETING AND TRANSFORMATION AND ITS IMPACT ON CONSUMER BUYING BEHAVIOR IN PAKISTAN: A STUDY OF CULTURAL DIFFERENCES AND OTHER FACTORS - Asma Shahzad; Dr. Muhammad Asim (International Journal of Contemporary Issues in Social Sciences, 2024)
This research investigates the current state of digital marketing and online shopping in Pakistan, focusing on consumer perceptions, platform reliability, and factors influencing online purchasing. Utilizing a sample of 250 participants, the study employs a quantitative methodology, including surveys and statistical analysis, to examine various aspects of digital marketing and online shopping. The findings reveal that digital marketing in Pakistan is predominantly at a middle stage (32.4%), with 26% of participants believing it has reached its peak and 20.8% advocating for further improvement. High prices are identified as the primary barrier preventing the middle class from engaging in online shopping (38%), although a significant portion finds traditional shopping preferable (18%). Safety concerns regarding the sharing of personal information online are mixed, with 34% of participants feeling it is safe, while 26.8% consider it unsafe. Daraz emerges as the most reliable online shopping platform (46.4%), followed by online stores (13.2%). The study also indicates a prevalent belief that the digital era has replaced traditional marketing methods (54.4%) and that social media plays a critical role in raising awareness about digitalization (60%). Participant satisfaction with online shopping is varied, with nearly 50% expressing a need for improvements. Online websites are the most frequently used platforms (50.8%), and online shopping is perceived as making it easier for people from diverse cultures to purchase their preferred products (53.6%). Despite mixed opinions on whether digital marketing effectively targets the right audience, personal factors are found to be the primary influence on online purchasing decisions (32%). This research proves that the digital marketing and online shopping is not stagnant and there is more potential in the future as well as identifying the potential shortcomings, exploring opportunities of growth and development in Pakistan.